Were the Tritaians (Pausanias 6.12.8-9) Arkadian? Pausanias at Work - Roy, James (Classica et Mediaevalia, 2026)
This article examines what knowledge of Arkadia Pausanias already had, and how he used that knowledge, when he sought to determine whether, as a victor-monument at Olympia claimed (Paus. 6.12.8-9), the polis Tritaia (known as Achaian) had ever been Arkadian.